Pengaruh Brand Image dan E-Wom Terhadap Keputusan Pembelian Konsumen Marketplace Shopee - Muhammad Riki; Roswaty Roswaty; Try Wulandari (CV. Ulil Albab Corp, 2024)
This study aims to analyze the effect of brand image and e-WOM on consumer purchasing decisions for the Shopee marketplace. Research is not limited to one specific place, but can include various locations that are relevant to the focus of the study (shopee marketplace users). The sampling used in this study was non-probability sampling using purposive sampling technique, there were 150 respondents. This research data was obtained from a questionnaire. The analysis technique used in this research is multiple linear regression method. Based on the results of the F test, the Fcount value is 120.781 with a Ftable value of 3.056 so that the Fcount> Ftable value (120.781> 3.056) with a significance level of 0.000> 0.05, it can be concluded that Brand Image (X1), e-WOM (X2) have a jointly significant effect on Purchasing Decisions (Y). Based on the results of the t test, it shows that Brand Image with a sig value of Brand Image (X1) on Purchasing Decisions (Y) is 0.000 <0.05 and the value of t count> t table is 4.885> 1.976. So it can be concluded that the Brand Image variable has a significant effect on Purchasing Decisions. E-WOM with a sig value of e-WOM (X2) on Purchasing Decisions is 0.000 <0.05 and t count> t table is 4.984> 1.976, it can be concluded that the e-WOM variable has an effect and is significant on Purchasing Decisions. Meanwhile, the results of the correlation coefficient (R) of brand image, e-wom on consumer purchasing decisions obtained a correlation coefficient value of 0.788 at a significance level of α 5%. While the result of the detemination coefficient (R2) obtained a value of 0.617. This shows that Brand imgae and e-WOM are able to explain the purchasing decision variable by 0.617 or 61.7%. And the remaining 38.3% can be explained / influenced by other variables not included in this study.